Passive Smoking is Associated with Risk of Early Onset of Cardiac Dysfunction - Abul-Fadl AM, Azza M.; Darweesh, Mohamed; Bishr, Nehad Taha; Amer, Eman Gamal; Al-Jawaldeh, Ayoub (International Journal of Scientific Research and Management (IJSRM), 2020)
Background: Second hand smoke (SHS) exposes infants and young children to many short and long term hazards. In adults PS was found to result in left sided diastolic dysfunction.Aim: To identify changes in the structure and function of the right side of the heart that can be influenced by exposure of infants to SHS.Methods: Echocardiographic evaluation of the right side of the heart was carried out for 75 infants aged 3 to 12 months of age; 39 were formula milk fed (FF) from birth and an age matched control of 36 breastfed  (BF) infants. A sub-analysis was done for each group in relation to exposure to PS. Measurements included Tricuspid annular plane excursion (TAPSE) and S’ wave for peak systolic annular velocity for right systolic function, E wave (early passive ventricular filling) and E/A ratio, tissue Doppler imaging (TDI) for E’ and A’ and E/E’ prime ratio for assessing ventricular filling pressure for diastolic dysfunction.Findings:  TDI in FF showed significantly higher values for E prime and E/E’ ratio in infants not exposed to SHS vs. those exposed to SHS (12.5±0.96 cm vs. 11.1±1.1 cm at P=0.000) and E/E’ (6.65±0.9 vs. 7.7±0.9 at P=0.003) respectively. There were no significant differences in systolic function (TAPSE) and S’ wave. However RV diameter was significantly higher in those exposed to SHS (1.3±0.09 cm) vs. no exposure (1.2±0.07 cm) at P